Fifty degrees below - Robinson, Kim Stanley 1952- (Bantam Books, 2005)
After years of denial and non-action, a near-future Earth faces a crossroad when it is threatened with the dire implications of global warming, an environmental crisis that ironically could unleash a devastating Ice Age on the planet.
Keywords: Science fiction.; Washington (D.C.) -- Fiction; Political fiction; Science fiction